Phenolic compounds and antioxidant, antimicrobial and antimycobacterial activities of Serjania erecta Radlk. (Sapindaceae) - Claudia Andréa Lima Cardoso; Roberta Gomes Coelho; Neli Kika Honda; Arnildo Pott; Fernando Rogério Pavan; Clarice Queico Fujimura Leite (Brazilian Journal of Pharmaceutical Sciences, 2013)
Serjania erecta Radlk.(Sapindaceae) is a medicinal plant traditionally used in Brazil. We assayed the ethanolic extract of leaves and roots against seven microorganisms. The REMA (Resazurin Microtiter Assay) assay was used to measure the biological activity in vitro against Mycobacterium tuberculosis and our results showed moderate activity of the ethanolic extract. On the other hand S. aureus, P. aeruginosa, S. setubal, C. albicans, S. cerevisiae and E. coli revealed that the leaves and roots of S. erecta inhibited the growth of all microorganisms. The ethanolic extracts of leaves and roots showed low values of antioxidant activities. The ethanolic extracts of leaves and roots were analyzed by chromatographic and spectrometric methods. (-)-Epicatechin, kaempferol aglycone and five glycoside derivates were isolated: kaempferol-3-O-α-L-rhamnopyranoside, kaempferol-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside from the roots and kaempferol, kaempferol 3,7-di-O-α-L-rhamnopyranoside, vitexin, isovitexin and (-)-epicatechin in the leaves. This is the first chemical study reported in the literature about this specie.